If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 14) + (2x + -4) = 60 Reorder the terms: (14 + 3x) + (2x + -4) = 60 Remove parenthesis around (14 + 3x) 14 + 3x + (2x + -4) = 60 Reorder the terms: 14 + 3x + (-4 + 2x) = 60 Remove parenthesis around (-4 + 2x) 14 + 3x + -4 + 2x = 60 Reorder the terms: 14 + -4 + 3x + 2x = 60 Combine like terms: 14 + -4 = 10 10 + 3x + 2x = 60 Combine like terms: 3x + 2x = 5x 10 + 5x = 60 Solving 10 + 5x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5x = 60 + -10 Combine like terms: 10 + -10 = 0 0 + 5x = 60 + -10 5x = 60 + -10 Combine like terms: 60 + -10 = 50 5x = 50 Divide each side by '5'. x = 10 Simplifying x = 10
| 25/100=x/4260 | | 5y-10+y+60=6y+50-3y | | y=-(x+3)(2x-7) | | -24a^5b^3/21a^2b | | 6+13s-4=7s+57-5s | | 20(x)=14(0.5) | | 12y-4y+3= | | 2c^2-16c+30=0 | | 2c^2-16c-30=0 | | 1/2(10−n)2n | | 5(5x+3)=-5(2x-5)+2x | | 3(4p+1)=7(p+9) | | -5(49x+12)=27(-30-x) | | 2(x-3)=39 | | 3+3u=12 | | 16x-2=15x+6 | | -15x-89=-63-25x | | N-20=7n+10 | | 6x+12=3x+75 | | 2(4x+2)=5x-32 | | 5p^2=60+20p | | 8p-15=4p-3 | | 2w+5=15-3w | | 3m-8m-6=64 | | 3/4x-3/8=1/2y | | 2p=14-5p | | 2x+4=106 | | 10(.30)=x(.5) | | x-12+6=2 | | -53-10x=101-45x | | 8x-15y=3 | | 10(.25)=x(.5) |